PENGARUH PUZZLE GAME TERHADAP PERSEPSI BELAJAR MATEMATIKA DI KOTA BATAM - Yoputra, Keaton; Anthony, Anthony; Utomo, Kevin Saputra; Evans, Felix; Mandala, Ivan Octovia (IKIP Siliwangi Bandung, 2023)
Initially regarded for entertainment purposes only, games have now evolved as a medium for learning. This research’s purpose is to investigate the effects of playing puzzle games towards leaning mathematics. This research uses the quantitative method through distributing questionnaires with senior high school and university students from Batam City as the target population. Linear regression technique is used for analyzing data. Results from this research indicate the variable challenge, engagement, and skill significantly affect the perceived learning of mathematics. This research concludes that puzzle games need to be challenging, fun, and interesting to increase the perceived learning of mathematics effectively. Skill in playing puzzle games could also improve the perceived learning in mathematics. Hence the players will increase their intuition and logical problem-solving ability.